On the rotational motion of NEAs during close encounters with the Earth - Boldrin, Luiz A. G. [UNESP]; Araujo, Rosana A. N.; Winter, Othon C. [UNESP] (Springer Nature, 2020)
During their lifetime, the Near-Earth Asteroids (NEAs) suffer numerous close encounters (CE) with Earth, Mars and Venus. It has been demonstrated that gravitational interactions during close planetary encounters can alter an asteroid’s spin state, and hence, along with collisions, play a role in the rotational evolution of NEAs. The variation of the rotational angular momentum during the encounters can increase or decrease the rotation rate depending on the initial condition. In addition to the rotation rate, close encounters cause variation in the movement of precession and nutation of the asteroid. Using a numerical model that takes into account the spin-orbit coupling of a body with ellipsoidal shape, the subject of this study is to analyze the rotational motion (rotation, precession and nutation) of asteroids during CE with the Earth for different initial conditions. We computed the variation of the obliquity and the variation of spin period after the CE. We found significant change in obliquity and spin period only in cases with strong encounter, that is in cases that the impact parameter of the encounter (1.2 ≤ d ≤ 7 (Earth radii) and the relative velocity (v) are small. Our results also show that the variation of rotational motion due to the close encounter is capable of tumbling the axis of rotation and gravitational rupture may occur in a few cases.